Discovery of attenuation effect of orexin 1 receptor to aversion of nalfurafine: Synthesis and evaluation of D-nor-nalfurafine derivatives and analyses of the three active conformations of nalfurafine. Issue 17 (1st September 2020) - Nagumo, Yasuyuki; Katoh, Koki; Iio, Keita; Saitoh, Tsuyoshi; Kutsumura, Noriki; Yamamoto, Naoshi; Ishikawa, Yukiko; Irukayama-Tomobe, Yoko; Ogawa, Yasuhiro; Baba, Takeshi; Tanimura, Ryuji; Yanagisawa, Masashi; et al.
Graphical abstract: Abstract: The D-nor-nalfurafine derivatives, which were synthesized by contraction of the six-membered D-ring in nalfurafine (1 ), had no affinity for orexin 1 receptors (OX1 Rs). The 17 N -lone electron pair in 1 oriented toward the axial direction, while that of D-nor-derivatives was directed in the equatorial configuration. The axial lone electron pair can form a hydrogen bond with the 14-hydroxy group, which could push the 6-amide side chain toward the downward direction with respect to the C-ring. The resulting conformation would be an active conformation for binding with OX1 R. The dual affinities of 1 for OX1 R and κ opioid receptor (KOR) led us to elucidate the mechanism by which only 1 showed no aversion but U-50488H. Actually, 1 selectively induced severe aversion in OX1 R knockout mice, but not in wild-type mice. These results well support that OX1 R suppresses the aversion of 1 . This is the elucidation of long period puzzle which 1 showed no aversion in KOR.